A novel GAA-repeat-expansion-based mouse model of Friedreich’s ataxia - Sara Anjomani Virmouni (Disease Models & Mechanisms, 2015)
Friedreich’s ataxia (FRDA) is an autosomal recessive neurodegenerative disorder caused by a GAA repeat expansion mutation within intron 1 of the FXN gene, resulting in reduced levels of frataxin protein. We have previously reported the generation of human FXN yeast artificial chromosome (YAC) transgenic FRDA mouse models containing 90–190 GAA repeats, but the presence of multiple GAA repeats within these mice is considered suboptimal. We now describe the cellular, molecular and behavioural characterisation of a newly developed YAC transgenic FRDA mouse model, designated YG8sR, which we have shown by DNA sequencing to contain a single pure GAA repeat expansion. The founder YG8sR mouse contained 120 GAA repeats but, due to intergenerational expansion, we have now established a colony of YG8sR mice that contain ~200 GAA repeats. We show that YG8sR mice have a single copy of the FXN transgene, which is integrated at a single site as confirmed by fluorescence in situ hybridisation (FISH) analysis of metaphase and interphase chromosomes. We have identified significant behavioural deficits, together with a degree of glucose intolerance and insulin hypersensitivity, in YG8sR FRDA mice compared with control Y47R and wild-type (WT) mice. We have also detected increased somatic GAA repeat instability in the brain and cerebellum of YG8sR mice, together with significantly reduced expression of FXN, FAST-1 and frataxin, and reduced aconitase activity, compared with Y47R mice. Furthermore, we have confirmed the presence of pathological vacuoles within neurons of the dorsal root ganglia (DRG) of YG8sR mice. These novel GAA-repeat-expansion-based YAC transgenic FRDA mice, which exhibit progressive FRDA-like pathology, represent an excellent model for the investigation of FRDA disease mechanisms and therapy.